Opinions of parents, teachers and school board members regarding healthy eating: A qualitative investigation of lay Thai people's perspectives - Korwanich K. (2014)
Background: The prevalence of overweight, obesity, and dental caries is increasing in Thai preschool children. Parents and teachers influence the diet of young children. Objective: To inform on, and be aware of what foods and drinks the children have consumed. Material and Method: The present qualitative study investigated attitudes and practices among parents, school board members and teachers regarding preschool children's eating behaviors and regarding factors influencing children to purchase snacks and beverages. One hundred and fifty five persons took part in 14 focus group discussions. Results: Regarding healthy eating in school, the participants were concerned only with the nutritional aspects of healthy eating and the specific foods eaten by the children. Factors influencing children's food choices included children's classmates, social factors, socioeconomic status, advertising, packaging, and marketing techniques. Conclusion: These results made parents, teachers, and school board members realize that their children faced problems regarding their diet and health, and need to seek out their own strategies about how to promote healthy eating among preschool children.